Relationship between hemoglobin levels and oral hygiene status in different trimesters of pregnancy - A cross-sectional study - Venkat Baghirath Pacha; Madhuri Mukhe; Hari Vinay Balisetty; P Parameswar Naishadham; Vijay Kumar Jogishetty; Bhargavi Krishna Ayinampudi (Wolters Kluwer Medknow Publications, 2019)
Background: Pregnancy is a phase which has gained much attention due to the physiological changes taking place, of which the oral health is of utmost importance as it may pose difficulties in birth outcomes. Aim: This study aims to evaluate the oral hygiene status with hemoglobin (Hb) concentration in each trimester and in each age group and to correlate between them. Materials and Methods: A randomized cross-sectional study was conducted on 1008 pregnant women of the age group 18-40 years who attended at the Government Maternity Hospital in Hyderabad. The individuals were screened for the oral health status, which includes oral hygiene index-simplified (OHI-S) and periodontal index (PI) by Russell. The blood sample was collected to evaluate hematological profile. The correlation between Hb levels and oral health status was evaluated by Chi-square and one-way ANOVA test using SPSS version software. The P < 0.05 was considered statistically significant. Results: The mean of OHI-S was 2.11 ± 0.514, PI was 2.61 ± 0.818, and Hb levels were 1.49 ± 0.500. There was a statistical significance between OHI-S (P < 0.025), PI (P < 0.014), and Hb levels (P < 0.710), respectively with the trimesters but not with the age groups. Therefore, the values for OHI-S and PI were higher in 3rd trimester when compared to other trimesters. Conclusion: The study suggests that there was a significant correlation between OHI-S, PI, and Hb levels within the trimesters of pregnancy irrespective of the age groups and Hb levels. The oral hygiene of examined women was satisfactory but is more at risk of periodontal diseases.